Effects of post-scenario debriefing versus stop-and-go debriefing in medical simulation training on skill acquisition and learning experience: a randomized controlled trial - Schober, Patrick; Kistemaker, Kay R. J.; Sijani, Fereshte; Schwarte, Lothar A.; van Groeningen, Dick; Krage, Ralf (BMC medical education, 2019)
Debriefing is a critical component to promote effective learning during simulation-based training. Traditionally, debriefing is provided only after the end of a scenario. A possible alternative is to debrief specific portions during an ongoing simulation session (stop-and-go debriefing). While this alternative has theoretical advantages, it is not commonly used due to concerns that interruptions disturb the fidelity and adversely affect learning. However, both approaches have not been rigorously compared, and effects on skill acquisition and learning experience are unknown. We randomly assigned 50 medical students participating in a simulation-based cardiopulmonary resuscitation training to either a post-scenario debriefing or stop-and-go debriefing. After four weeks, participants performed a repeat scenario, and their performance was assessed using a generic performance score (primary outcome). A difference of 3 or more points was considered meaningful. A 5-item questionnaire was used to assess the subjective learning experience and the perceived stress level (secondary outcomes). There was no significant difference between the groups for the performance score (mean difference: -0.35, 95%CI: -2.46 to 1.77, P = 0.748, n = 48). The confidence limits excluding the specified relevant 3-point difference suggest equivalence of both techniques with respect to the primary outcome. No significant differences were observed for secondary outcomes. Stop-and-go debriefing does not adversely affect skill acquisition compared to the classic post-scenario debriefing strategy. This finding is reassuring when interruptions are deemed necessary and gives simulation instructors the latitude to tailor the timing of the debriefing individually, rather than adhering to the unsupported dogma that scenarios should not be interrupted. As this study is not a clinical trial, it was not registered in a clinical trials register.